2011
DOI: 10.1001/jama.2011.697
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Mortality, Length of Stay, and Preventable Complications Among Critically Ill Patients Before and After Tele-ICU Reengineering of Critical Care Processes

Abstract: In a single academic medical center study, implementation of a tele-ICU intervention was associated with reduced adjusted odds of mortality and reduced hospital length of stay, as well as with changes in best practice adherence and lower rates of preventable complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
266
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(285 citation statements)
references
References 37 publications
10
266
2
7
Order By: Relevance
“…Moreover, many authors have reported that patients enrolled in telemedicineenabled ICU programs experience improved clinical outcomes, reductions in complications, and improved evidence-based bundle compliance compared with those not enrolled in programs. [15][16][17][18] Our study has several limitations. First, we did not randomize the children to receive Family-Link, and therefore the potential confounding biases may exist.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, many authors have reported that patients enrolled in telemedicineenabled ICU programs experience improved clinical outcomes, reductions in complications, and improved evidence-based bundle compliance compared with those not enrolled in programs. [15][16][17][18] Our study has several limitations. First, we did not randomize the children to receive Family-Link, and therefore the potential confounding biases may exist.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11] To improve the quality of critical care and extend the reach of the current intensivist workforce, at least 40 health-care systems in the United States have implemented telemedicine programs in ICUs (tele-ICUs). [12][13][14][15] Tele-ICUs typically combine real-time videoconferencing, telemetry, and electronic health records (EHRs). A tele-ICU allows physician and nurse intensivists located in a centralized monitoring center to monitor and care for patients in multiple distant ICUs.…”
mentioning
confidence: 99%
“…Care at hospitals with low annual sepsis case volumes is associated with increased mortality, whereas care at hospitals with intermediate annual case volumes is not associated with worse mortality compared with hospitals with high annual case volumes. Future efforts toward the dissemination of best practices to LV hospitals (19), ICU outreach programs using telehealth technology (57), and/or regionalization of sepsis care (21,22,58) may all be important strategies to eliminate existing disparities. Important barriers exist, which could limit the effectiveness of each strategy, and, at this time, the optimal approach is not known.…”
Section: Resultsmentioning
confidence: 99%